Emergency Management - Eksioglu, Burak (IntechOpen, 2012)
After the large-scale disasters that we have witnessed in the recent past, it has become apparent that complex and coordinated emergency management systems are required for efficient and effective relief efforts. Such management systems can only be developed by involving many scientists and practitioners from multiple fields. Thus, this book on emergency management discusses various issues, such as the impact of human behavior, development of hardware and software architectures, cyber security concerns, dynamic process of guiding evacuees and routing vehicles, supply allocation, and vehicle routing problems in preparing for, and responding to large scale emergencies. The book is designed to be useful to students, researchers and engineers in all academic areas, but particularly for those in the fields of computer science, operations research, and human factor. We also hope that this book will become a useful reference for practitioners.